Sexualised drug taking among men who have sex with men: a systematic review. (January 2019) - Tomkins, Andrew; George, Ryan; Kliner, Merav
Aims: Sexualised drug taking is increasingly reported on national and international levels. We aim to review existing evidence of the relationship between recreational drug use (RDU) and sexual intercourse among men who have sex with men (MSM). Methods: We reviewed published abstracts and full articles identified from Cochrane, MEDLINE and Embase databases from November 2010 to 2017. We included any existing studies investigating RDU in MSM and at least one of the following: high-risk sexual practices, sexually transmitted infections (STIs) or barriers to accessing specialist support. Results: In total, 112 studies were included. Of them, 38 studies specifically reported the prevalence of chemsex-related drug use. Links with sexualised drug taking and high-risk sexual practices including condomless sex and group sex were reported by several studies. Recreational drug use in the sexual setting appears linked to the acquisition of STIs, including hepatitis C, syphilis and gonorrhoea. Reports of adverse mental health outcomes are increasingly described, with several studies documenting chemsex-related inpatient admission. A paucity of research addressing barriers to those accessing specialist drug support services was identified. Conclusion: This review demonstrates the complex interplay between recreational drug use, high-risk sexual practices and STIs. It identifies the description of adverse mental health outcomes in the chemsex setting, thus highlighting the need for a multidisciplinary approach across specialties in the management of those adversely affected. Finally, it illuminates the need for future research into perceived barriers of those who require access to support services to ensure timely and comprehensive support provision.